Mandela : the authorized biography - Sampson, Anthony, 1926-2004. (New York, N.Y. : Knopf, 1999)
"The Life of Nelson Mandela is one of the most extraordinary epics of the twentieth century. An almost-forgotten prisoner on Robben Island twenty years ago, apparently doomed to a helpless existence as a victim of apartheid, he not only survived but almost single-handedly saved South Africa from potential chaos, to become one of the most widely admired leaders in the world. Mandela's myth is dazzling; in this biography Anthony Sampson penetrates it to show us the man himself."--BOOK JACKET.
"Mandela is filled with new insights and information. We see how prison, which he and his fellow inmates turned into a kind of unofficial university, gradually transformed Mandela from a headstrong activist into a reflective and consummately skilled statesman. We learn how British and American diplomats cold-shouldered him when support was desperately needed, and about the political infighting, sometimes vicious, that went on between anti-apartheid factions.
Particularly fascinating is Sampson's narrative of the incredible negotiations leading to Mandela's release from prison and the eventual collapse of the white regime, when his colleagues feared that he was selling out to the government."--BOOK JACKET.
"At every turn, this book sheds fresh light on the moral dilemmas that Mandela was forced to face again and again in his personal and public lives. In the struggle for freedom for South African blacks, he paid a tragic price, becoming alienated from his wife and remote from his children.
Yet he famously retained his humanity, and while Sampson does not conceal Mandela's failings - his stubbornness, his fixed loyalties, his princely manners and detachment - the man who emerges is authentically heroic."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Mandela, Nelson, -- 1918-2013.; Presidents -- South Africa -- Biography; South Africa -- Politics and government -- 20th century